Режимы сжигания органоводоугольных топлив; Химия твердого топлива; № 2 - Валиуллин Т. Р. Тимур Радисович; Вершинина К. Ю. Ксения Юрьевна; Лырщиков С. Ю. Сергей Юрьевич; Шевырёв С. А. Сергей Александрович (2018, 2018)
Заглавие с экрана